2005
DOI: 10.1081/ncn-200061865
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Novel Peptide Nucleic Acid-Peptide Chimera for Non-Invasive Imaging of Cancer

Abstract: A chelator-peptide-PNA-peptide chimera specific for KRAS has been prepared by continuous solid phase coupling with a C-terminal insulin-like growth factor 1 (IGF1) ligand, D(cys-ser-lys-cys), and N-terminal bis(S-benzoyl thioglycoloyl) diaminopropanoate chelator for radionuclide labeling. The probe was purified by RP-HPLC and characterized by MALDI-TOF mass spectroscopy. The probe was labeled with 99mTc and 64Cu. Both labeled probes accumulated in human pancreatic cancer xenografts in immunocompromised mice. C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 7 publications
0
26
0
Order By: Relevance
“…DO3A-KRAS chelator PNA-peptide radiohybridization probes (Table 1) were labeled with 64 Cu essentially as described. 28 Briefly, 20 mg of DO3A-PNA-peptide (~4.5 nmol) dissolved in 15 mL of water was added to 200 mL of 0.1 M NH 4 OAc, pH 5.5 and vortexed. Then, 2 mL of 64 CuCl 2 (7.4-11.1 MBq, or 200-300 mCi, ~1 nmol) (MDS Nordion, Kanata ON, Canada) in 0.1 M HCl, was added to the mixture and incubated for 15 min.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…DO3A-KRAS chelator PNA-peptide radiohybridization probes (Table 1) were labeled with 64 Cu essentially as described. 28 Briefly, 20 mg of DO3A-PNA-peptide (~4.5 nmol) dissolved in 15 mL of water was added to 200 mL of 0.1 M NH 4 OAc, pH 5.5 and vortexed. Then, 2 mL of 64 CuCl 2 (7.4-11.1 MBq, or 200-300 mCi, ~1 nmol) (MDS Nordion, Kanata ON, Canada) in 0.1 M HCl, was added to the mixture and incubated for 15 min.…”
Section: Methodsmentioning
confidence: 99%
“…We reported previously that a KRAS PNA-peptide nanoparticle that included the N 2 S 2 chelator bis(S-benzoyl-thioglycoloyl) diaminopropanoate labeled with 99m Tc permitted scintigraphic imaging of immunocompromised mice bearing pancreas cancer xenografts. 28 However, positron emission tomography (PET) is more sensitive than single photon emission computed tomography (SPECT). 29 Therefore we hypothesized that 64 Cu [half-life, 12.7 h; b + , 653 keV, 38%] chelated to an N 4 O 2 chelator 1,4,7-tris(carboxymethylaza) cyclododecane-10-azaacetyl (DO3A) coupled to a KRAS PNA-peptide hybridization probe could enable sensitive PET imaging of KRAS mRNA in pancreas cancer xenografts.…”
Section: Introductionmentioning
confidence: 99%
“…80 In this study, a true enzymatic behaviour was demonstrated when an efficient turnover of RNA substrate was shown with a 100-fold excess of substrate. 80 Another interesting approach has been introduced by Panyutin et al, 81 who reported the sequencespecific DNA strand cleavage by incorporation of the Auger electron-emitting radionuclide 111 In into PNA oligomers. More specifically, they conjugated diethylene triamine pentaacetic acid (DTPA) to PNA oligomers before chelating them with 111 Indeed, since organic functional groups of some proteins are exploited in recognition of nucleobases of nucleic acids, nucleobases of PNAs may be conversely used in the recognition of proteins.…”
Section: Metal-containing Pnas As Artificial Nucleasesmentioning
confidence: 99%
“…80 Another interesting approach has been introduced by Panyutin et al, 81 who reported the sequencespecific DNA strand cleavage by incorporation of the Auger electron-emitting radionuclide 111 In into PNA oligomers. More specifically, they conjugated diethylene triamine pentaacetic acid (DTPA) to PNA oligomers before chelating them with 111 Indeed, since organic functional groups of some proteins are exploited in recognition of nucleobases of nucleic acids, nucleobases of PNAs may be conversely used in the recognition of proteins. 87 In other words, the PNA was employed as the potential binding site by protein recognition of derivatives of purine.…”
Section: Metal-containing Pnas As Artificial Nucleasesmentioning
confidence: 99%
See 1 more Smart Citation